Russian Financial and Economic System Behavior Depending on Interest Rate Scenario - Valery V. SMIRNOV; Nina G. GUBANOVA; Natalia V. BONDARENKO; Polina G. GORBUNOVA; Tamara V. TALANOVA (Communications of International Proceedings, 2020)
The study is bases on a systematic approach applying the method of statistical analysis. The study exposess sharpening of negative behaviour of  Russian financial and economic system resulting from the drop in interest rate: national currency devaluation, lower tax revenues, etc., bringing about the necessity to increase M2 and need for bigger volumes of devaluated rouble consumer loan raising GDP deflator. Positive behaviour of the Russian financial and economic system is attributed to the sustainability of the Russian Federation Central Bank replenishing its gold and foreign currency reserves and maintaining trade balance (trade surplus) increasing its strength under the conditions of decrease in world oil prices and Covid-19 pandemic. It has been found out that positive behaviour of Russian financial and economic system is reached due to the decrease in interest rate, rather than its invariably low level. The limit of positive behavior of the Russian financial and economic system depending on interest rate scenario is determined through volatility of crude oil and natural gas prices. Decreasing interest rate and simultaneous devaluation of the national currency the Central Bank maintains the structure of commodity economy strengthening the positions at the periphery of the world capitalism and maintaining the status of energy superpower, thus increasing its sustainability in relation to the drop in world oil prices.
Keywords: Capitalism; Behavior; Interest Rate; Financial and Economic System.